2015
DOI: 10.1080/13854046.2015.1054437
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cognitive Performance on the Cogstate Brief Battery When Taken In-Clinic, In-Group, and Unsupervised

Abstract: These results suggest that cognitive testing with the CBB in alternate settings can provide valid cognitive data comparable to data obtained during individually supervised testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 32 publications
2
54
0
Order By: Relevance
“…The advantage of administration of the CogState in a clinical setting is that a supervisor can help participants understand the task during the practice session. Participants assessed in an unsupervised research setting may be more easily distracted, show sub-optimal effort and motivation, or may have lower scores due to inadequate understanding of the task [37]. However, the CogState is increasingly administered in an unsupervised or home setting [13, 37, 38], making it less labor-intensive and less costly than a supervised clinical setting and standard pencil and paper testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of administration of the CogState in a clinical setting is that a supervisor can help participants understand the task during the practice session. Participants assessed in an unsupervised research setting may be more easily distracted, show sub-optimal effort and motivation, or may have lower scores due to inadequate understanding of the task [37]. However, the CogState is increasingly administered in an unsupervised or home setting [13, 37, 38], making it less labor-intensive and less costly than a supervised clinical setting and standard pencil and paper testing.…”
Section: Discussionmentioning
confidence: 99%
“…Participants assessed in an unsupervised research setting may be more easily distracted, show sub-optimal effort and motivation, or may have lower scores due to inadequate understanding of the task [37]. However, the CogState is increasingly administered in an unsupervised or home setting [13, 37, 38], making it less labor-intensive and less costly than a supervised clinical setting and standard pencil and paper testing. It has been shown that there were no differences in results between supervised and unsupervised settings [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35,37] Moreover, Cogstate has been shown to be a sensitive indicator of early cognitive deficits. [35] Cogstate performance has been found to be similar in supervised and unsupervised settings, [39] and the feasibility and utility of an unsupervised, online administration of the brief battery has been demonstrated in a large population-based sample. [34] Internet speed does not affect Cogstate performance data because the Cogstate tasks are first loaded via the Internet and then run locally on a participant’s computer.…”
Section: Methodsmentioning
confidence: 99%
“…The CogState standardized battery [http://cogstate.com/computerized-tests/cognitive-tests/battery] was chosen due to its high test-retest reliability and negligible practice effects in healthy individuals across different exam settings (Cromer et al, 2015; Falleti et al, 2006). Task performance (speed or accuracy as per Maruff et al, 2009) was contrasted pre- vs. post-training within subjects using paired t-tests.…”
Section: Methodsmentioning
confidence: 99%